2014
DOI: 10.4321/s1135-57272014000600002
|View full text |Cite
|
Sign up to set email alerts
|

Características generales de los artículos originales incluidos en las revisiones bibliográficas sobre salud e inmigración en España

Abstract: RESUMENFundamentos: La realidad socio-demográfica configurada en España a partir de la incorporación de la población inmigrante requiere analizar las necesidades y prioridades generadas por esta situación en todos los ámbitos, incluido el de la investigación en salud. El objetivo del presente estudio es conocer las características generales de los artículos incluidos en una revisión bibliográfica sobre este tema y realizada en el marco del Subprograma de Salud e Inmigración del CIBERESP Métodos: Revisión bibli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
4
1
1
Order By: Relevance
“…This indicates that, even though migrants are coming from countries where the prevalence of communicable diseases is higher than in Ireland, [38] researchers in Ireland who set out to generate empirical data about migrant health to date do not appear to have directed their attention to negative and risky aspects of migrant health for the host population. These findings are in contrast with Spanish research, [36] which highlights that the research landscape on migrant health can vary considerably by country/migrant population group. This points to the WHO-SAAP as a helpful framework to elucidate the approaches to migrant health research within and across countries, as well as its role in identifying research gaps.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This indicates that, even though migrants are coming from countries where the prevalence of communicable diseases is higher than in Ireland, [38] researchers in Ireland who set out to generate empirical data about migrant health to date do not appear to have directed their attention to negative and risky aspects of migrant health for the host population. These findings are in contrast with Spanish research, [36] which highlights that the research landscape on migrant health can vary considerably by country/migrant population group. This points to the WHO-SAAP as a helpful framework to elucidate the approaches to migrant health research within and across countries, as well as its role in identifying research gaps.…”
Section: Discussioncontrasting
confidence: 99%
“…The finding that a large number of studies focused on the social determinants of health, public health preparedness and health system adaptations (strategic areas 3, 4 and 5), with a smaller number focused on communicable diseases and health screening (strategic areas 6 and 8), contrasts with the results of a previous scoping review on migrant health in Spain, which found that the epidemiology of infectious diseases was the predominant theme [36]. Similarly, a review of research on the health of Latin-American migrants in Europe found that the largest proportion of research focused on communicable diseases (38%), with few studies addressing health determinants, including health service use (8%) and broader structural and socio-economic factors (7%) [37].…”
Section: Discussionmentioning
confidence: 88%
“…The dramatic changes in demographics, socio-economics and politics require an update of the analysis of health service utilization by immigrants in order to properly determine the breadth and scope of the current situation. Consequently, research on migrant access and utilization of health services has proliferated in recent decades [ 8 , 9 ]. Results from a previous review point to a lower utilization rate of general and specialist medical services by immigrants compared to native-born populations [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…People immigrate mainly in search of better living conditions, settling down in the hosting country for a long period of time or permanently [1]. In Spain, the immigration boom started at the turn of the millennium [2] but in Catalonia, it has been continuously on the rise since the 1980s [3]. Until 2012, access to health care in Spain involved uncomplicated administrative procedures, was free of charge and guaranteed emergency care for all citizens [4].…”
Section: Introductionmentioning
confidence: 99%